IMPLEMENTASI KEBIJAKAN PENGENDALIAN KEBAKARAN HUTAN DAN LAHAN DI PROVINSI SUMATERA SELATAN - Kushartati Budiningsih (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2017)
Land and forest fires in Indonesia occur almost every year since 1997. The main causes of fires are due to human activities, driven by El Nino during dry season and biophysical conditions of degraded land. In Indonesia land and forest fires have an impact on socio-cultural, economic and political aspects. Therefore, Indonesian government involves multi institutions to control land and forest fire. Thus, to manage fire, coordination among institutions is absolutely necessary. This study using qualitative approach to analyze coordination among government agencies in term of land and forest fire control with case in South Sumatera Province. The results showed that coordination among government agencies occured in the context of fire suppression and the performance was less than optimal when viewed from the achievement of fire fighting targets. Factors influenced the coordination of fire management were authority, communication, controlling and leadership. Therefore, need to be improved by considering that fire suppression in peatlands is relatively difficult.